Total Amino Acids and Protein Concentrate of Sea Cucumber (Stichopus vastus) From Natuna Waters, Riau Islands. Issue 1 (1st December 2022) - Sukmiwati, M; Sari, N I; Edison, E
Abstract: Sea cucumbers haven't been utilized optimally, and have a high economic value, due to high protein content of meat. This research aims to know the proximate content and total amino acids of sea cucumber flour, and total amino acids of protein concentrate of sea cucumber. The result showed that different ratios of flour and solvent have a significant effect on protein concentrate. Proximate content and protein concentrate with the ratio of flour and solvents (1:3) are protein 74.25%, moisture 10.58%, ash 7.25%, carbohydrate 6.47%, crude fiber 2.66%, and fat 0.16%. Total amino acids protein concentrate (1:3) is 53.59%. The major amino acids protein concentrate are glutamic acid, glycine, alanine, and aspartic acid. Ratios of flour and solvent (1:4) are protein content 76.13%, moisture 10.35%, ash 7.17%, carbohydrate 6.03%, crude fiber 2.51% and fat 0.13%. Total amino acids protein concentrate (1:4) is 56.74%. The major amino acids in protein concentrate are glycine, glutamic acid, alanine, and arginine. Ratios of flour and solvent (1:5) are protein 77.35%, moisture 9.14%, ash 6.67%, carbohydrate 6.00%, crude fiber 2.45%, and fat 0.10% respectively. Total amino acids protein concentrate (1:5) is 61.63%. The major amino acids protein concentrate are glycine, glutamic acid, aspartic acid, and alanine.